2017
DOI: 10.1016/j.jvs.2016.10.120
|View full text |Cite
|
Sign up to set email alerts
|

Five-year outcomes of the PYTHAGORAS U.S. clinical trial of the Aorfix endograft for endovascular aneurysm repair in patients with highly angulated aortic necks

Abstract: The U.S. PYTHAGORAS trial of the Aorfix endograft is the first EVAR clinical trial to include a majority of highly angulated (≥60 degrees) infrarenal aortic necks and is the first to produce evidence after 5 years of implantation. Despite predictors of worse short- and long-term outcomes, pertinent outcomes were better than or similar to those of trials with less severe anatomy. These results support the use of this "on-label" endovascular option, particularly in patients with highly angulated aortic neck anat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 27 publications
1
30
0
Order By: Relevance
“…18) From another point of view, De Bock et al reported using the in vitro test to show that proximal kinking of the device can occur and result in the presence of type Ia endoleak in an angle between the suprarenal aorta and proximal neck above 60°. 14) Similar to previous studies, [12][13][14][15][16][17] the current study revealed that the incidence of persistent type Ia endoleak was higher in the angulated group, while its freedom rate for persistent type Ia endoleak was found to be significantly lower (p=0.010). This fact indicated that countermeasures against severe proximal neck angulation during EVAR should be mandatory.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…18) From another point of view, De Bock et al reported using the in vitro test to show that proximal kinking of the device can occur and result in the presence of type Ia endoleak in an angle between the suprarenal aorta and proximal neck above 60°. 14) Similar to previous studies, [12][13][14][15][16][17] the current study revealed that the incidence of persistent type Ia endoleak was higher in the angulated group, while its freedom rate for persistent type Ia endoleak was found to be significantly lower (p=0.010). This fact indicated that countermeasures against severe proximal neck angulation during EVAR should be mandatory.…”
Section: Discussionsupporting
confidence: 89%
“…As the predictors for sac enlargement, several studies have reported the neck angle >60° was only predictable, but other degrees have yet to be investigated. [12][13][14][15][16][17] The subgroup comparison in our study, limited to the angulated group, was conducted for the proximal neck angle of 60°, the angle for the IFU. Interestingly, the rates of freedom from sac enlargement indicated no difference between the two groups, and proximal neck angle >47° was again identified as the threshold for developing late sac enlargement even if the AAA was within the IFU.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 The 87.8% compliance rate with clinical follow up in the ENGAGE registry was within the 87e98% rate that has been reported in other EVAR clinical trials. 34,39,45…”
Section: Limitationsmentioning
confidence: 99%
“…In current practice, specialized stent-graft devices and equipment are used to cope with unfavorable neck anatomy. However, there have been reported heterogeneous results regarding their effectiveness and longterm outcomes [21][22][23].…”
Section: Discussionmentioning
confidence: 99%